Pengaruh Profitabilitas, Nilai Tukar dan Tingkat Suku Bunga terhadap Harga Saham Perusahaan Sub Sektor Batubara - Hasibuan, David H.M.; Marpaung, Annaria Magdalena; Marpaung, Bintang Sahala; Rivai, Abdul (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The coal sector is the main producer in Indonesia, which is the largest exporter in Asia and Europe. The coal sub-sector has high prospects because most of the energy sources for power plants use coal as an energy source. Indonesia has abundant potential resources, especially mining which plays an important role in driving the country's economy. This creates jobs, guarantees the country's energy security and increases the country's foreign exchange earnings. This research was conducted to examine the effect of Profitability, Exchange Rates and Interest Rates in the coal sub-sector companies on the IDX. There are 20 populations of coal mining companies listed on the IDX. The sample of this research is 8 companies' financial reports obtained by using purposive sampling method. The analytical method used is panel data regression analysis . The results showed that Return on Equity has a positive effect on stock prices, while the exchange rate and interest rates have no effect on stock prices. Simultaneously Return On Equity, Exchange Rates and Interest Rates have a joint effect on Stock Prices.